2016
DOI: 10.1167/16.8.17
|View full text |Cite
|
Sign up to set email alerts
|

The influence of image content on oculomotor plasticity

Abstract: When we observe a scene, we shift our gaze to different points of interest via saccadic eye movements. Saccades provide high resolution views of objects and are essential for vision. The successful view of an interesting target might constitute a rewarding experience to the oculomotor system. We measured the influence of image content on learning efficiency in saccade control. We compared meaningful pictures to luminance and spatial frequency-matched random noise images in a saccadic adaptation paradigm. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 37 publications
(41 reference statements)
5
28
2
Order By: Relevance
“…These results lend further support to the recent discussion that saccadic adaptation involves more than a simple, automatic, error-based, low-level motor learning process (Collins & Wallman, 2012;Herman, Blangero, Madelain, Khan, & Harwood, 2013; LevyBencheton, Pisella, Salemme, Tilikete, & Pelisson, 2013;Madelain, Paeye, & Wallman, 2011;Meermeier et al, 2016;Panouilleres et al, 2014;Schütz & Souto, 2015;Zimmermann & Lappe, 2016). The top-down modulation on adaptation of scanning saccades observed in the present study may originate from frontal cortical areas or from the basal ganglia.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These results lend further support to the recent discussion that saccadic adaptation involves more than a simple, automatic, error-based, low-level motor learning process (Collins & Wallman, 2012;Herman, Blangero, Madelain, Khan, & Harwood, 2013; LevyBencheton, Pisella, Salemme, Tilikete, & Pelisson, 2013;Madelain, Paeye, & Wallman, 2011;Meermeier et al, 2016;Panouilleres et al, 2014;Schütz & Souto, 2015;Zimmermann & Lappe, 2016). The top-down modulation on adaptation of scanning saccades observed in the present study may originate from frontal cortical areas or from the basal ganglia.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those of Meermeier et al (2016), who found an increased amount of adaptation but no difference in learning rate when comparing meaningful images of female human figures with luminance-and spatial-frequency-matched noise. Hence, both comparisons (image to noise and novel to repeating stimuli) resulted in a higher amount of saccadic adaptation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations